Altruism in The Happy Prince and Other Tales: (A Moral Discourse Analysis) - Ratri Pratna Lestari (ELITE: Journal of English Language and Literature, 2017)
This research aimed to analyze altruism in the main character of The Happy Prince and Other Tales short stories collection used altruism in terms of empathy theory by Batson (2011). The objective of the research was to describe how altruism in terms of empathy was used in the short stories. The researcher used descriptive qualitative as the research method. The data source was short stories of The Happy Prince and Other Tales as the primary data. The technique of data was carried out by downloading, reading intensively, coding, and reducing the data. The technique of data analysis was carried out by presenting, describing, interpreting, and concluding research results. Based on the findings and discussion of this research, showed that altruism really existed and was applied by the main characters. The researcher found 14 data containing an aspect of altruism in terms of empathy concern, antecedents of empathy, and behavioral consequences. Empathy concern was a motivation that encourages altruism. Then, Antecedents of empathy concern were the second factor that drives altruism in the short stories. The last aspect was the behavioral consequences, the end of the consequences of altruism that occurred in short stories.